Match outcome and distances covered at various speeds in match play by elite German soccer players - Andrzejewski, M.; Konefal, M.; Chmura, P.; Kowalczuk, E.; Chmura, J. (International Journal of Performance Analysis in Sport, 2016)
The aim of the present study is to examine how various playing positions and end result (i.e. won, drawn or lost match) affect the total covered distance and distances covered at low and high-intensity by German Bundesliga soccer players. Match performance data were collected from 350 soccer players competing in the German Bundesliga during the 2014/2015 domestic season. A total of 4393 individual match observations were undertaken on outfield players. The analysis was carried out using the Impire AG motion analysis system recording all movements of players in all 306 matches. The examined variables included total distance covered and distance covered in low-intensity and high-intensity running. The analysis of distance covered at high intensity shows that central defenders and full-backs covered shorter distances in won matches than in lost matches (p = 0.01). Furthermore, forwards covered significantly longer distances in won matches than in drawn and lost matches (p = 0.05). In conclusion, the results indicate the importance of considering match outcome and playing positions in the assessment of physical aspects of soccer players' performance.